Improving Properties of Tungsten Oxide Films by Gamma Ray Irradiation - Hanoon, Mustafa K.; Nasir, Eman M. (Iraqi Journal of Science, 2024)
The deposition process and investigation of the physical properties of tungsten trioxide (WO3) thin films before and after gamma irradiation are presented in this paper. The WO3 thin films were deposited, using the pulse laser deposition technique, on glass substrates at laser energies of 600mJ and 800mJ. After deposition, the samples were gamma irradiated with Co60. The structural and optical properties of polycrystalline WO3 thin films are presented and discussed before and after 5kGy gamma irradiation at the two laser energies. X-ray diffraction spectra revealed that all the films consisted of WO3 crystallized in the triclinic form; the dislocation density and lattice strain increased with the absorbed dosage of gamma irradiation. The optical constants, the average diameter and the surface roughness of the WO3 films were calculated before and after gamma irradiation and for the two laser energies. It was found that the WO3 thin films conductivity increased by γ-irradiated and with the increase of the laser energy.